2021
DOI: 10.1136/bmjopen-2020-045568
|View full text |Cite
|
Sign up to set email alerts
|

Identification and categorisation of relevant outcomes for symptomatic uncomplicated gallstone disease: in-depth analysis to inform the development of a core outcome set

Abstract: BackgroundMany completed trials of interventions for uncomplicated gallstone disease are not as helpful as they could be due to lack of standardisation across studies, outcome definition, collection and reporting. This heterogeneity of outcomes across studies hampers useful synthesis of primary studies and ultimately negatively impacts on decision making by all stakeholders. Core outcome sets offer a potential solution to this problem of heterogeneity and concerns over whether the ‘right’ outcomes are being me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“… 20 , 34 Better understanding and consensus on patient-centered outcomes of importance across the stages and complications of gallstone disease may guide such concerted and complementary approaches to preventing and modifying the persistent metabolic, biologic, behavioral, structural, social, and economic etiologies upstream from the preventable clinical etiologies of morbidity, mortality, and disability with dGD. 35 37 …”
Section: Discussionmentioning
confidence: 99%
“… 20 , 34 Better understanding and consensus on patient-centered outcomes of importance across the stages and complications of gallstone disease may guide such concerted and complementary approaches to preventing and modifying the persistent metabolic, biologic, behavioral, structural, social, and economic etiologies upstream from the preventable clinical etiologies of morbidity, mortality, and disability with dGD. 35 37 …”
Section: Discussionmentioning
confidence: 99%
“…This study utilized articles published only in the English language, which may have prevented the identification of some PROM tools used in LC. Four gallstone-disease-specific PROMs have been developed 54 . The present search did not identify any gallstone-specific PROMs; however, these do not seem to have gained traction in LC as they have not been utilized in the recent literature.…”
Section: Discussionmentioning
confidence: 99%
“…This phase of outcome mapping has been published elsewhere 3 . In brief, a systematic literature review was conducted to identify outcomes reported in trials of interventions for symptomatic uncomplicated gallstone disease, and outcomes from exploratory studies reported by patients with a lived experience of symptomatic uncomplicated gallstone disease.…”
Section: Methodsmentioning
confidence: 99%
“…A recent in-depth analysis 3 of outcomes that had been reported or were considered relevant to symptomatic gallstone disease highlighted the significant variability between studies. In addition, outcome mapping also included empirical research that identified new, unreported in this context, outcomes of importance 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation